Spatial planning and the European Union : Europeanisation from within - Purkarthofer, Eva (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"European Union policies are intertwined with all sectors of public administration and governance in the member states, including spatial, urban and regional planning. Legal regulations like the Natura 2000 Directives, funding programmes associated with EU Cohesion Policy or strategies such as the Territorial Agenda 2030 all leave their mark on planning - yet with considerably different effects in Europe's cities and regions. This book serves as a guide to navigate the connection points between EU policies and spatial planning by introducing the logics of EU policymaking and European spatial planning, outlining the most relevant EU policies with relevance for spatial planning and presenting examples from Austria and Finland how EU policies are applied in domestic contexts. By exploring the Europeanisation of spatial planning 'from within', the book acknowledges how differential ideas about what spatial planning is and what role the EU plays therein shape the actualised impacts of EU policies. By providing a comprehensive perspective on the relevance of the European Union for spatial planning, this book is ideal for students, academics and administrators who want to grasp how the EU shapes and affects planning practice in Europe's cities and regions"--
Keywords: Regional planning -- European Union countries; European Union countries -- Government policy; Land use -- Europe -- Planning; POLITICAL SCIENCE / Public Policy / Regional Planning; BUSINESS & ECONOMICS / Urban & Regional